Perbedaan Efektivitas Media Video dan Leaflet Terhadap Pengetahuan Santri Tentang Skabies - Khania Atika (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Scabies is a skin disease caused by infection with the mite Sarcoptes scabiei hominis variety. Scabies is easily contagious and is closely related to the number of people living together in one place. Cases of scabies are still commonly found in Indonesia, especially in densely populated environments. The level of knowledge affects the incidence of scabies because knowledge plays an important role in preventing scabies transmission. Increased knowledge can be done through counseling. However, appropriate counseling media tools are needed so that the information received becomes long-term memory. This study assesses the differences in the effectiveness of video media and leaflets on students' knowledge of scabies in Dayah Ar Raudhah Tahfizh Al-Qur'an, Blang Mangat District, Lhokseumawe City. This study involved 60 students with a quasi-experimental research type and the research design was one group pretest-posttest. The sampling technique used simple random sampling. The results of this study there are significant differences in the level of knowledge before and after counseling both with video media and leaflet media with a p value of 0.000 (<0.05) using the Wilcoxon test while the results of the study of differences in media effectiveness using the Mann Whitney test with p value = 0.004 (p<0.05), which means that there are differences in the effectiveness of video media and leaflets. The conclusion of this study is that video media is more effective than leaflet media in increasing students' knowledge about scabies.